Lipoprotein(a) as a risk factor for atherosclerotic cardiovascular disease in patients in non-metropolitan areas of Brandenburg, Germany - Hillmeister, Philipp; Li, Kangbo; Dai, Mengjun; Sacirovic, Mesud; Pagonas, Nikolaos; Ritter, Oliver; Bramlage, Peter; Bondke Persson, Anja; Buschmann, Ivo; Zemmrich, Claudia (Frontiers in Cardiovascular Medicine, 2024)
Background and aims In the non-metropolitan region of Brandenburg (Germany), which is characterized by high rates of cardiovascular diseases and underserved medical care, there is a lack of awareness regarding lipoprotein(a) [Lp(a)] as a risk factor. In addition, data from patients with atherosclerotic cardiovascular disease (ASCVD) in diverse regional backgrounds, including the understudied Brandenburg cohort, and various healthcare statuses remain insufficient. Methods In this WalkByLab study, Lp(a) levels were monitored in a non-metropolitan cohort (n = 850) in Brandenburg, Germany, comprising 533 patients at high cardiovascular risk and 317 healthy controls. Patients underwent a comprehensive angiological screening, which included blood serum analysis, assessment of medical and family history, cardiovascular risk, and disease status, and evaluation of lifestyle and quality of life. All parameters were evaluated with regard to two groups based on Lp(a) levels: low (<50 mg/dl) and high (≥50 mg/dl). Results Brandenburg patients with cardiovascular diseases showed higher Lp(a) levels than healthy controls (24.2% vs. 14.8%, p = 0.001). Logistic regression analysis with different characteristics revealed that Lp(a) was an independent risk factor significantly associated with ASCVD (OR 2.26, 95% CI 1.32–3.95, p = 0.003). The high-Lp(a) group showed a higher proportion of patients with coronary artery disease, peripheral artery disease, or cerebrovascular disease compared to the low-Lp(a) group (50% vs. 36.8%; 57.7% vs. 45.8%; 17.6% vs. 9.2%; p = 0.004); also, a higher percentage of patients in the high-Lp(a) group had heart failure (72.8% vs. 53.2%, p = 0.014) and myocardial infarction (24.7% vs. 13.9%, p = 0.001). The high-Lp(a) group exhibited higher rates of statins (63.1% vs. 50.4%, p = 0.003), ezetimibe (14.8% vs. 5.5.%, p = 0.001), and beta-blockers (55.7% vs. 40.7%, p = 0.001) use. Lp(a) levels were found to be independent of physical activity or smoking behavior and did not change over time (12 months). Conclusions Our study highlights the significance of elevated Lp(a) levels in Brandenburg cardiovascular patients and identifies them as an independent risk factor for ASCVD, which has implications for addressing cardiovascular health of non-metropolitan populations.